Preliminary Study on the Connection Between the Mineral Profile of Horse Hooves and Tensile Strength Based on Body Weight, Sex, Age, Sampling Location, and Riding Disciplines - Rueda-Carrillo, Gabriel; Rosiles-Martínez, René; Hernández-García, Anaid Ireri; Vargas-Bello-Pérez, Einar; Trigo-Tavera, Francisco J. (Frontiers in Veterinary Science, 2022)
Hoof mineral profile is important as it could affect locomotion. Factors such as body weight, sex, age and riding disciplines affects hooves mineral profile. In Mexico and globally, studies are needed on the characterization of mineral profile of hooves and tensile strength, as this could help to prevent overgrowth or microfractures. Therefore, in the present survey, 165 samples of equine hoof cuttings from different sex, ages, breeds, and riding disciplines from different regions of Mexico were analyzed for their mineral composition and a universal testing machine was used to measure tensile strength. More than half of the samples were from males (63%) and aged 3 to 5 years (52%). Most samples were obtained from horses use for reproduction (36%) and working (29%) purposes. The most preponderant minerals were K (3416 µg/g), Na (2242 µg/g) and Ca (631 µg/g). Tensile strength ranged from 1.2 to 45 N. Females had higher (P<0.05) amounts of Zn than males. Animals younger than 3 years old have lower (P<0.05) levels of Na than those between 3 and 5 years old. Horses used for reproduction had lower (P<0.05) Mg concentrations than animals used for running and working. Tensile strength was similar between demographic characteristics. Horses from Santa Gertrudis military ranch had higher (P<0.05) levels of Ca, Se and Na compared with horses from other sampling location. Cupper was higher (P<0.05) in horses from racecourse. Potassium was higher (P<0.05) in horses from the Presidential General Staff. Overall, there was no evident connection between sex, ages, breeds, and riding disciplines from different regions of Mexico and the mineral composition of the hoof or its tensile strength. Further research should focus on the relation on specific feeding regimes, horse individual characteristic, hoof mineral contents and tensile strength.